The effects of spatially varying earthquake impacts on mood and anxiety symptom treatments among long-term Christchurch residents following the 2010/11 Canterbury earthquakes, New Zealand. (September 2016) - Hogg, Daniel; Kingham, Simon; Wilson, Thomas M.; Ardagh, Michael
Abstract: This study investigates the effects of disruptions to different community environments, community resilience and cumulated felt earthquake intensities on yearly mood and anxiety symptom treatments from the New Zealand Ministry of Health's administrative databases between September 2009 and August 2012. The sample includes 172, 284 long-term residents from different Christchurch communities. Living in a better physical environment was associated with lower mood and anxiety treatment rates after the beginning of the Canterbury earthquake sequence whereas an inverse effect could be found for social community environment and community resilience. These results may be confounded by pre-existing patterns, as well as intensified treatment-seeking behaviour and intervention programmes in severely affected areas. Nevertheless, the findings indicate that adverse mental health outcomes can be found in communities with worse physical but stronger social environments or community resilience post-disaster. Also, they do not necessarily follow felt intensities since cumulative earthquake intensity did not show a significant effect.